ASSESSMENT OF THE PHYSICAL ENDURANCE OF HIGHER STUDENT IN SPORT AT NATIONAL SPORTS ACADEMY "VASSIL LEVSKI", BULGARIA - Sofka POPOVA (Editura Universitatii Transilvania din Brasov, 2019)
The quality of endurance is of essential importance for achieving high sports results. It is namely that importance that has provoked the scientific studies of a range of researchers, as well as particularly our interest in it. The purpose of the paper is to establish the level of the physical endurance of women and men higher students at "V. Levski" National Academy of Sport" in the city of Sofia, Bulgaria. A modified Cooper test - running a distance of 2413 m is made use of as a basic method of study. The analysis of the results we have received provides us with the reason about the following summary: the persons under study are of a high level of general status of physical endurance; the level of the women high students' physical endurance is better than the level of the men higher students under study; the physical endurance level of the track and field competitors is better in comparison to the other kinds of sports.